2009
DOI: 10.1029/2008jd009969
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Moderate Resolution Imaging Spectroradiometer (MODIS) albedo retrieval algorithm: Dependence of albedo on solar zenith angle

Abstract: [1] The Moderate Resolution Imaging Spectroradiometer (MODIS) bidirectional reflectance distribution function (BRDF)/albedo algorithm uses multiday, multiband MODIS surface reflectance products from Terra and Aqua to produce a global albedo product at a 500 m resolution (Collection 5). This paper evaluates the ability of the MODIS albedo product to represent albedos at all diurnal solar zenith angles through a comparison with field measurements from the Surface Radiation Budget Network (SURFRAD) and the Atmosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
168
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(176 citation statements)
references
References 27 publications
8
168
0
Order By: Relevance
“…Errors arise from the MODIS retrievals themselves and the inference from these of values appropriate to the ATSR scene and spectral response. The assumed 0.2 fractional error and 0.4 correlation values are broadly consistent with the accuracy reported in (Liu et al, 2009). Further consideration of the use of MODIS albedo data in the ORAC scheme is given in (Sayer et al, 2011b).…”
Section: Measurement Vector and Covariancesupporting
confidence: 62%
“…Errors arise from the MODIS retrievals themselves and the inference from these of values appropriate to the ATSR scene and spectral response. The assumed 0.2 fractional error and 0.4 correlation values are broadly consistent with the accuracy reported in (Liu et al, 2009). Further consideration of the use of MODIS albedo data in the ORAC scheme is given in (Sayer et al, 2011b).…”
Section: Measurement Vector and Covariancesupporting
confidence: 62%
“…To match this data perfectly to the CLARA-SAL black-sky albedo, we would need to remove all diffuse flux contributions (resulting from atmospheric scattering), and also account for any possible absorption effects in the direct flux. However, Liu et al (2009) showed in their study that the difference between black-sky and blue-sky albedo is very small in cloudfree conditions when SZA is less than 70 degrees. Manninen et al (2012) showed that the difference between black-sky and blue-sky albedo measurements on the ground at Cabauw in the Netherlands is typically no more than 5 %, although the difference increases with increasing AOD.…”
Section: Validation Against Ground Truthmentioning
confidence: 99%
“…While MODIS albedo products at local solar noon are used in the previous section albedo evaluation, MODIS BRDF/albedo parameters retrieved are more appropriate for WRF/CMAQ simulations with changing solar zenith angle (SZA, θ Sun ). The MODIS product can be used to characterize the actual albedo at a location throughout the better part of the diurnal cycle with some confidence based on the study by Liu et al [2009]. Although many surface conditions (such as soil conditions, canopy, surface heterogeneity, and spatial scale) affect surface albedo; direct-beam albedo may be predominately influenced by SZA [Yang et al, 2008].…”
Section: Modis Datamentioning
confidence: 99%